Alterations in Multi‐Scale Cardiac Architecture in Association With Phosphorylation of Myosin Binding Protein‐C. Issue 3 (15th March 2016) - Taylor, Erik N.; Hoffman, Matthew P.; Barefield, David Y.; Aninwene, George E.; Abrishamchi, Aurash D.; Lynch, Thomas L.; Govindan, Suresh; Osinska, Hanna; Robbins, Jeffrey; Sadayappan, Sakthivel; Gilbert, Richard J.
Abstract : Background: The geometric organization of myocytes in the ventricular wall comprises the structural underpinnings of cardiac mechanical function. Cardiac myosin binding protein‐C (MYBPC3) is a sarcomeric protein, for which phosphorylation modulates myofilament binding, sarcomere morphology, and myocyte alignment in the ventricular wall. To elucidate the mechanisms by which MYBPC3 phospho‐regulation affects cardiac tissue organization, we studied ventricular myoarchitecture using generalized Q‐space imaging (GQI). GQI assessed geometric phenotype in excised hearts that had undergone transgenic (TG) modification of phospho‐regulatory serine sites to nonphosphorylatable alanines (MYBPC3 AllP−/(t/t) ) or phospho‐mimetic aspartic acids (MYBPC3 AllP+/(t/t) ). Methods and Results: Myoarchitecture in the wild‐type (MYBPC3 WT ) left‐ventricle (LV) varied with transmural position, with helix angles ranging from −90/+90 degrees and contiguous circular orientation from the LV mid‐myocardium to the right ventricle (RV). Whereas MYBPC3 AllP+/(t/t) hearts were not architecturally distinct from MYBPC3 WT, MYBPC3 AllP−/(t/t) hearts demonstrated a significant reduction in LV transmural helicity. Null MYBPC3 (t/t) hearts, as constituted by a truncated MYBPC3 protein, demonstrated global architectural disarray and loss in helicity. Electron microscopy was performed to correlate the observed macroscopic architectural changes with sarcomere ultrastructure and demonstrated that impaired phosphorylation of MYBPC3 resulted in modifications of the sarcomere aspect ratio and shear angle. The mechanical effect of helicity loss was assessed through a geometric model relating cardiac work to ejection fraction, confirming the mechanical impairments observed with echocardiography. Conclusions: We conclude that phosphorylation of MYBPC3 contributes to the genesis of ventricular wall geometry, linking myofilament biology with multiscale cardiac mechanics and myoarchitecture.